Medicarpin, a Natural Pterocarpan, Heals Cortical Bone Defect by Activation of Notch and Wnt Canonical Signaling Pathways. - Manisha Dixit; Ashutosh Raghuvanshi; Chandra Prakash Gupta; Jyoti Kureel; Mohd Nizam Mansoori; Priyanka Shukla; Aijaz A John; Kavita Singh; Dipak Purohit; Pallavi Awasthi; Divya Singh; Atul Goel (PLoS ONE, 2015)
We evaluated the bone regeneration and healing effect of Medicarpin (med) in cortical bone defect model that heals by intramembranous ossification. For the study, female Sprague-Dawley rats were ovariectomized and rendered osteopenic. A drill hole injury was generated in mid femoral bones of all the animals. Med treatment was commenced the day after and continued for 15 days. PTH was taken as a reference standard. Fifteen days post-treatment, animals were sacrificed. Bones were collected for histomorphometry studies at the injury site by micro-computed tomography (μCT) and confocal microscopy. RNA and protein was harvested from newly generated bone. For immunohistochemistry, 5μm sections of decalcified femur bone adjoining the drill hole site were cut. By μCT analysis and calcein labeling of newly generated bone it was found that med promotes bone healing and new bone formation at the injury site and was comparable to PTH in many aspects. Med treatment led to increase in the Runx-2 and osteocalcin signals indicating expansion of osteoprogenitors at the injury site as evaluated by qPCR and immunohistochemical localization. It was observed that med promoted bone regeneration by activating canonical Wnt and notch signaling pathway. This was evident by increased transcript and protein levels of Wnt and notch signaling components in the defect region. Finally, we confirmed that med treatment leads to elevated bone healing in pre-osteoblasts by co localization of beta catenin with osteoblast marker alkaline phosphatase. In conclusion, med treatment promotes new bone regeneration and healing at the injury site by activating Wnt/canonical and notch signaling pathways. This study also forms a strong case for evaluation of med in delayed union and non-union fracture cases.